2004
DOI: 10.1186/1471-2458-4-10
|View full text |Cite
|
Sign up to set email alerts
|

"New Choices" for women with addictions: perceptions of program participants

Abstract: Background: Substance use in pregnancy is a major public health problem. It can have profound effects on pregnancy outcomes, and childhood health and development. Additionally, women who use substances have their own health-related issues. Although intervention is important, these women often have difficulty using traditional systems of care. The New Choices program is a centralized, multi-sector approach to service delivery that has attempted to overcome barriers to care by offering one-stop shopping in a sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 47 publications
3
57
0
2
Order By: Relevance
“…The New Choices program is an example of a comprehensive outpatient integrated program in a large urban centre in Canada that offers a "one-stop shop" for women with substance use issues who are pregnant or parenting young children (Niccols & Sword, 2005;Sword, Niccols, & Fan, 2004). New Choices was launched in 1998 by staff from several agencies in Hamilton (i.e., a hospital-based women's detoxification center, a community-based addiction service, an infant development program, a children's mental health agency, a home for adolescent mothers, a family resource center, a child care center, the public health department, and child protection services) with donations of services-in-kind and some government funding.…”
Section: New Choicesmentioning
confidence: 99%
“…The New Choices program is an example of a comprehensive outpatient integrated program in a large urban centre in Canada that offers a "one-stop shop" for women with substance use issues who are pregnant or parenting young children (Niccols & Sword, 2005;Sword, Niccols, & Fan, 2004). New Choices was launched in 1998 by staff from several agencies in Hamilton (i.e., a hospital-based women's detoxification center, a community-based addiction service, an infant development program, a children's mental health agency, a home for adolescent mothers, a family resource center, a child care center, the public health department, and child protection services) with donations of services-in-kind and some government funding.…”
Section: New Choicesmentioning
confidence: 99%
“…As part of a preliminary evaluation of New Choices, interviews were conducted with programme participants to gain an in-depth account of their experiences in the programme and perceptions of any changes that could be attributed to programme involvement (Sword, Niccols, & Fan 2004). The interviews' emergent themes captured women's motivations for attending New Choices, benefits of participation and overall quality of the programme.…”
mentioning
confidence: 99%
“…It is also possible that the provision of gender-sensitive services may attract more women to a treatment program. Indeed, research has found that women cite lack of child care as a barrier to entering treatment (Grant, 1997) and that SUD programs' provision of child care is an important facilitator in women's treatment process (Howell & Chasnoff, 1999;Sword et al, 2004).…”
Section: Discussionmentioning
confidence: 99%